Conservation of Australian Rainforest Plant Species Utilising Cryopreservation. - Hardstaff, Lyndle Kay (Curtin University, 2023)
The physiological characteristics of many Australian rainforest species prevent their conservation using traditional seed-banking methods. Alternative conservation strategies such as cryopreservation and tissue culture were investigated for nine threatened rainforest taxa. Regeneration after cryopreservation was achieved for five species from three families. Survival without regeneration was achieved for a further two species. These results provide hope for the long-term conservation of these and other rainforest species with similar characteristics.